2023
DOI: 10.1038/s12276-022-00911-z
|View full text |Cite
|
Sign up to set email alerts
|

Stable colonization of Akkermansia muciniphila educates host intestinal microecology and immunity to battle against inflammatory intestinal diseases

Abstract: Gut microbial preparations are widely used in treating intestinal diseases but show mixed success. In this study, we found that the therapeutic efficacy of A. muciniphila for dextran sodium sulfate (DSS)-induced colitis as well as intestinal radiation toxicity was ~50%, and mice experiencing a positive prognosis harbored a high frequency of A. muciniphila in the gastrointestinal (GI) tract. Stable GI colonization of A. muciniphila elicited more profound shifts in the gut microbial community structure of hosts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 59 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…Nevertheless, the therapeutic efficacy of A. muciniphila was not completely satisfactory depending on its colonization . Previous studies have shown that A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the therapeutic efficacy of A. muciniphila was not completely satisfactory depending on its colonization . Previous studies have shown that A.…”
Section: Discussionmentioning
confidence: 99%
“…muciniphila can significantly relieve acute colitis in mice. , Furthermore, the beneficial effect of A. muciniphila depends on the colonization rate. , Therefore, we investigated the effect of 2′FL and A. muciniphila alone or as synbiotics against colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Akk, on top of ameliorating mucosal inflammation caused by DSS via the microbe–host interaction by enhancing gut barrier function, reduces the levels of inflammatory cytokines and elevates the diversity of the microbial community [ 97 ]. For instance, stable gastrointestinal tract colonization of Akk contributed to the therapy and prognosis of inflammatory intestinal diseases induced by DSS and intestinal radiation via changing the host gut microbial community structure, facilitating proliferation and reprogramming the gene expression profile of Lactobacillus murinus [ 103 ]. Similarly, cadmium usually induces intestinal damage, and treatment with Akk effectively ameliorates intestinal mucosal damage by producing melatonin [ 104 ].…”
Section: Akkermansia Muciniphila : An Anti-inflammatory and ...mentioning
confidence: 99%
“…Furthermore, two kinds of sulfate-degrading microorganisms have been described in the bacteria kingdom: (i) Sul dogenic, such as Desulfovibrio spp. or Bilophila spp, which use sulfate as a nal electron acceptor to generate energy and produce inorganic hydrogen sul de (HS) as an end-product that can be toxic when produced in large amounts and has been associated with IBD pathogenesis [18]; (ii) Sulfate assimilatory, including A. muciniphila, that consume energy to incorporate Sulfate in several organic compounds, including peptides and amino acids and may produce secondary metabolites which can be used as a carbon source for other commensal bacteria [19]. The A. muciniphila genome recovered from a metagenome sample (B238) from a mouse consuming Emmental revealed a complete Sulfur assimilatory pathway.…”
Section: Homeostasis Contextmentioning
confidence: 99%
“…murinus. This bacterium has shown promising probiotic properties in treating intestinal in ammation disorders; and a recent study has reported its ability to alleviate DSS-induced colitis in mice [19], [26]. Another crucial functional impact of Emmental-type cheese consumption in mice with DSS-induced colitis was the increased diversity of sugars and amino acids uptake systems (ABC transporters systems and phosphotransferases systems) found in Lg murinus MAG, suggesting an improved capacity to adapt and assimilate different kinds of nutrients.…”
Section: In Ammation Contextmentioning
confidence: 99%